Estudios sobre la historia social de las ciencias y origen de la Escuela Normal Superior de Colombia (2009)
The present paper constitutes a partial report of the results until now obtained, del investigation project "the conceptions that based the initial formation of professors of sciences on the Superior Normal School of Colombia, from its beginning to 1952" stand out the dominant conceptions and its foundation of the denominated social studies of science or sociology is fitted inside del knowledge. Reference to made investigations is done that show the thought class that dominated in Colombia with respect to the technologies and the studied problem of the paper of Mutis in the introduction of Newtonian dynamics in the “Virreinato La Nueva Granada”. In the same way, it is alluded to the social history of chemistry in the country, in regard to which the creation of the chemistry studies, obeyed to the same cultural, political and economic conditions that gave origin to the Superior Normal School of Colombia